Analisis Efektivitas Program Rumah Anak Prestasi Bagi Anak Disabilitas di Kota Surabaya - Alvi Ismatul Hawa; Agus Widiyarta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Surabaya as a city that has won the main ranking of Child Friendly City for six consecutive times and received the highest points, continues to innovate programs that uphold the fulfillment of children's rights, especially children with disabilities who still need more attention to get their social welfare. The Surabaya City Government has inaugurated the “Rumah Anak Prestasi” program which was established in 2022 as to fulfill the rights of children with disabilities in Law Number 8 of 2016 and make Surabaya a complete Child-Friendly City. Rumah Anak Prestasi provide health services and skills training that can be followed free of charge for children with disabilities in Surabaya City. This research method is descriptive qualitative with a focus on analyzing the effectiveness of the Rumah Anak Prestasi program for children with disabilities in Surabaya City, referring to Budiani's (2007) Program Effectiveness theory which includes target accuracy, socialization, objectives, and program monitoring. The data collection technique of this research is through interviews, observation, and documentation. Rumah Anak Prestasi is an effective program for children with disabilities in that the objectives can be achieved and program monitoring is done well. However, the obstacles faced are the socialization of program information dissemination and parents' lack of understanding so that the accuracy of program targets has not covered all children with disabilities. Evaluation of the UPTD Kampung Anak Negeri of Surabaya City is needed regarding the improvement of program socialization so that it can attract all children with disabilities in Surabaya.